1977
DOI: 10.1136/jcp.30.7.620
|View full text |Cite
|
Sign up to set email alerts
|

Novobiocin and the differentiation of peptococci and peptostreptococci.

Abstract: SUMMARY Paper discs containing 5 /tg of novobiocin were used as a presumptive test to differenitiate peptococci and peptostreptococci. Zone diameters were measured and minimum inhibitory concentrations (MIC) of the antibiotic for each group were performed to ascertain the activity of the antibiotic against these genera. All strains of peptococci showed no zone of inhibition in the disc test together with an MIC of 25 ,ug/ml or greater. All strains of peptostreptococci showed zones of inhibition of at least 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…They were then inoculated onto lysed-blood medium and incubated in air and anaerobically for 3 days. All obligate anaerobes were identified by gram staining followed by antibiograms when necessary (Leigh and Simmons, 1977;Wren, Eldon and Dakin, 1977). The density of bacteria on the periurethral surface was calculated in terms of number of bacteria per cm2 by counting the number of colonies transferred from the gelatin cylinder and multiplying by a factor of 14 (Cooper et al, 1980).…”
Section: Methodsmentioning
confidence: 99%
“…They were then inoculated onto lysed-blood medium and incubated in air and anaerobically for 3 days. All obligate anaerobes were identified by gram staining followed by antibiograms when necessary (Leigh and Simmons, 1977;Wren, Eldon and Dakin, 1977). The density of bacteria on the periurethral surface was calculated in terms of number of bacteria per cm2 by counting the number of colonies transferred from the gelatin cylinder and multiplying by a factor of 14 (Cooper et al, 1980).…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies in this laboratory have shown that unbroken primary incubation for 48 h may be an important phase in the cultural process (Wren, et al, 1977a;Wren, 1977). The present study shows that only 29% of the cultivable anaerobic flora in a group of specimens can be isolated after incubation for 24 h and 60% after 48 h by the CONV system.…”
Section: Discussionmentioning
confidence: 99%
“…The anaerobes were characterised on the basis of morphology in gram-stained smears, fermentation pattern (Holdeman et al, 1977) after growth in cooked meat medium (Lab-m Ltd, Ford Lane, Salford), and result profile in API 20A (API Ltd, Farnborough, Hants;Hauser and Zabransky, 1976). Additional tests used for P. anaerobius were sensitivity to novobiocin (Wren, Eldon and Dakin, 1977) and liquoid (Wideman ef al., 1976); API 20A was not used for this organism.…”
Section: Methodsmentioning
confidence: 99%